Inclusión de la “Metodología Multicriterio” en el campo de la valoración de bienes inmuebles - Murillo-Navarro, Álvaro (Instituto Tecnológico de Costa Rica, 2010)
The subject is the valuation of the land, by using the Multicriterio Method, which are a series of mathematics and statistics procedures that reduces the expert subjectivity and help him to have a bigger view for obtain the right price for the ground. The main objective is research what this is and how can be used by the Diquís Hydroelectric Project (PHED), also establish by examples an easy and practical guide for develop the Multicriterio Method. The bibliographical research and the interviews with ICE and others companies’ experts can define the start and elaborate a process to put in practice the new way of valuation. Two real examples of proprieties are used for applicants the Multicriterio Method. As conclusions based on the Results and Theoretic Resume this methodology is perfectly adapted to national reality and the purposes of the PHED, which is trying to find the better way of buy all the proprieties affected, also all this process are flexible and no requires a high development software.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica. Escuela de Ingeniería en Construcción, 2010.
Keywords: Peritaje; Avalúo; Proyecto; Limitantes; Díquis